Remarkable recovery in a patient with intradural extramedullary haemangiopericytoma: a case report and literature review - Wang, Hongxiang; Wang, Liangzhe; Lu, Yicheng; Lu, Chengyin; Xu, Tao; Yan, Yong; Chen, Juxiang (Folia Neuropathologica, 2018)
Haemangiopericytomas (HPCs) in the spinal canal are extremely rare and have only been infrequently reported. Severe and sustained spinal cord compression resulting from these intraspinal tumours may cause potentially irreversible neurological impairment. We described a rare case of primary intradural extramedullary HPC recovered from serious compression of thoracic spinal cord in a 65-year-old man suffered from a rapidly progressive disease with complete paralysis of the lower limbs. Magnetic resonance imaging (MRI) and spinal angiography exhibited an unusual hypervascular mass, which was confirmed as HPC by pathological examination, in the dorsal aspects of T7 to T8 spine. Total surgical resection was performed followed by adjuvant radiation. Moreover, this patient had been undergoing specific training of lower limbs from the onset of paralysis and continuous rehabilitation was conducted after discharge. Increased strength of his lower limb muscles was shown in the period of follow-up. Remarkably, four years after surgery, this patient was able to walk with sticks. No signs of local recurrence or metastasis occurred. Conclusively, surgical removal is still the preferred treatment for HPC, and adjuvant radiotherapy and/or chemotherapy may help control tumour recurrence or metastasis. Additionally, it is possible that rehabilitation training potentially promotes neurological function recovery to some extent.